A quantitative analysis of microalgal lipids for optimization of biodiesel and omega‐3 production. Issue 8 (9th February 2013) - Olmstead, Ian L.D.; Hill, David R.A.; Dias, Daniel A.; Jayasinghe, Nirupama S.; Callahan, Damien L.; Kentish, Sandra E.; Scales, Peter J.; Martin, Gregory J.O.
Abstract The lipid characteristics of microalgae are known to differ between species and change with growth conditions. This work provides a methodology for lipid characterization that enables selection of the optimal strain, cultivation conditions, and processing pathway for commercial biodiesel production from microalgae. Two different microalgal species, Nannochloropsis sp. and Chlorella sp., were cultivated under both nitrogen replete and nitrogen depleted conditions. Lipids were extracted and fractionated into three major classes and quantified gravimetrically. The fatty acid profile of each fraction was analyzed using GC–MS. The resulting quantitative lipid data for each of the cultures is discussed in the context of biodiesel and omega‐3 production. This approach illustrates how the growth conditions greatly affect the distribution of fatty acid present in the major lipid classes and therefore the suitability of the lipid extracts for biodiesel and other secondary products. Biotechnol. Bioeng. 2013; 110: 2096–2104. © 2013 Wiley Periodicals, Inc.